International review of cell and molecular biology. (International Review of Cell and Molecular Biology, 2018)
International Review of Cell and Molecular Biology. Volume 336 reviews and details current advances in cell and molecular biology. The IRCMB series has a worldwide readership, maintaining a high standard by publishing invited articles on important and timely topics that are authored by prominent cell and molecular biologists. This updated volume includes specific chapters on Membrane trafficking in autophagy, Targeting the metabolism of leukemic cells, Autophagic flux in Alzheimer's disease, Transcriptional alterations associated with celiac disease, and the Regulation of antitumor immunity by IDO1, amongst other timely topics. The articles published in IRCMB have a high impact and an average cited half-life of 9 years. This great resource ranks high amongst scientific journals dealing with cell biology.